Chemical castration as a punishment in Peru: A bioethical dilemma between dignity, autonomy, and consent - Chávez-Torres, Alondra Silvana (2025)
This paper critically analyzes the viability of chemical castration as a penalty for sexual offenders from a bioethical and legal perspective. It argues that this measure is contrary to fundamental principles such as human dignity, personal autonomy, and informed consent, all of which are essential in any medical intervention that modifies a person's body. To this end, all the bills submitted to the Congress of the Republic of Peru between 2016 and 2024 proposing the incorporation of chemical castration as a criminal sanction for sexual offenders have been reviewed and analyzed. The analysis identified eight bills presented during the period under study, all of which exhibit serious normative deficiencies, lack of a clear legal framework, and violate constitutional guarantees. Furthermore, it is noted that these legislative proposals respond more to a logic of social revenge and punitive populism than to a genuine purpose of rehabilitation or social reintegration of the offender, which is openly incompatible with the principles and values governing a constitutional state governed by the rule of law. Moreover, it is argued that chemical castration does not constitute an effective measure to address the structural causes of sexual violence and could even generate counterproductive effects for offenders, victims, and society in general.